PENGGUNAAN PENDEKATAN PROGRAM FUZZY UNTUK MENYELESAIKAN MASALAH PROGRAM LINEAR MULTI-OBJEKTIF DAN APLIKASINYA PADA MASALAH TRANSPORTASI - , LISA SARAS WATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fuzzy programming approach is a method to find the optimal solution of multi objective linear programming problems. In this method a decision is taken by a decision maker, depending on the weight taken. Formulation of fuzzy programming approach is done by forming a marginal evaluation for each objective function and the global evaluation for all objective functions. Using ordinary optimization technique, we solve the fuzzy programming approach model to obtain a Pareto optimal solution (optimal compromise solution) at which the synthetic membership degree of global evaluation is maximum. Furthermore, will be given a multi objective transportation problem solving as a form of the multi objective linear programming problem using fuzzy programming approach. Numerical example will be also given to show the efficiency of the fuzzy programming approach.